2013
DOI: 10.1007/s00253-013-5397-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the extremophilic Deinococcus geothermalis DSM 11302 using co-substrate fed-batch culture

Abstract: Deinococcus geothermalis metabolism has been scarcely studied to date, although new developments on its utilization for bioremediation have been carried out. So, large-scale production of this strain and a better understanding of its physiology are required. A fed-batch experiment was conducted to achieve a high cell density non-limiting culture of D. geothermalis DSM 11302. A co-substrate nutritional strategy using glucose and yeast extract was carried out in a 20-L bioreactor in order to maintain a non-limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Several published results have reported that Deinococcaceae are proteolytic microorganisms and prefer other carbon sources than glucose in yeast extract and tryptone, like amino acids [ 2 , 28 ]. With a D. geothermalis strain, the best growth performances described to date have been obtained using a glucose-yeast extract co-substrate fed-batch culture [ 15 ]. So, five solutions were supplemented to the basal defined medium: a solution containing yeast extract vitamins, a casamino acid vitamin-free solution providing all the essential amino acids except tryptophan, and three cellular extracts; the results are shown in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several published results have reported that Deinococcaceae are proteolytic microorganisms and prefer other carbon sources than glucose in yeast extract and tryptone, like amino acids [ 2 , 28 ]. With a D. geothermalis strain, the best growth performances described to date have been obtained using a glucose-yeast extract co-substrate fed-batch culture [ 15 ]. So, five solutions were supplemented to the basal defined medium: a solution containing yeast extract vitamins, a casamino acid vitamin-free solution providing all the essential amino acids except tryptophan, and three cellular extracts; the results are shown in Table 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Only two works reported high cell density production of Deinococcaceae strains, e.g., Deinococcus radiodurans and Deinococcus geothermalis . The cultures were performed in a 20 L fermentor with a medium containing yeast extract [ 15 , 16 ]. Although previous works have shown that Deinococcaceae have complex nutritional requirements [ 2 , 13 , 17 , 18 ], no study has been reported yet on the influence of the inoculum preparation on their growth properties (growth rate, maximal biomass concentration, glucose uptake).…”
Section: Introductionmentioning
confidence: 99%